2012
DOI: 10.1007/s10592-012-0339-9
|View full text |Cite
|
Sign up to set email alerts
|

Variable rates of random genetic drift in protected populations of English yew: implications for gene pool conservation

Abstract: Protecting populations in their natural habitat allows for the maintenance of naturally evolved adaptations and ecological relationships. However, the conservation of genetic resources often requires complementary practices like gene banks, translocations or reintroductions. In order to minimize inbreeding depression and maximize the adaptive potential of future populations, populations chosen for ex situ conservation should be selected according to criteria that will result in a reduction of global coancestry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 57 publications
6
19
0
Order By: Relevance
“…According to the sex allocation theory, females are generally less competitive than males and females of English yew may have a higher mortality (Iszkuło et al, 2009). As shown in our earlier study, both populations reveal a significant SGS at six nuclear microsatellite markers (Chybicki et al, 2011) as well as relatively high genetic variation and no signal of a recent bottleneck (Chybicki et al, 2012). In addition, Cisy Staropolskie showed low (that is, F = 0.04), but statistically significant inbreeding (Chybicki et al, 2011).…”
Section: Natural Populationssupporting
confidence: 58%
See 2 more Smart Citations
“…According to the sex allocation theory, females are generally less competitive than males and females of English yew may have a higher mortality (Iszkuło et al, 2009). As shown in our earlier study, both populations reveal a significant SGS at six nuclear microsatellite markers (Chybicki et al, 2011) as well as relatively high genetic variation and no signal of a recent bottleneck (Chybicki et al, 2012). In addition, Cisy Staropolskie showed low (that is, F = 0.04), but statistically significant inbreeding (Chybicki et al, 2011).…”
Section: Natural Populationssupporting
confidence: 58%
“…Our previous study showed, for example, that Cisy Staropolskie are characterised by apparently lower ratio of effective (N e ) to census population size (N) than Cisy w Czarnem (N e /N = 0.033 vs 0.40, respectively; Chybicki et al, 2012) that could not be explained simply by differences in sex proportions. In addition, population histories, including possible variation of sex ratios, remain unknown except for the genetic evidence of no recent bottleneck (Chybicki et al, 2012). Thus, although the observed SGS patterns seem to reflect differences in sex proportions between the populations, we postulate to treat the conclusions with caution.…”
Section: Theoretical Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar reasons could lead to the elevated inbreeding estimate in the case of Las Mariański, which represented the most admixed gene pool in the region of lower species abundance. Alternative explanation would be a specific colonisation history, if a few (related) adult trees gave a rise to the population (Pujol et al 2009;Chybicki et al 2012). However, because no signatures of a strong bottleneck were revealed, the hypothesis of bottleneck has no support from the data.…”
Section: Discussionmentioning
confidence: 93%
“…Protection of populations in their natural habitat (in situ) maintains ecological and evolutionary processes, as well as adaptation (Chybicki et al 2012). However, the conservation of endangered and threatened tree species often requires proactive ex situ practices, such as the establishment of seed orchards, gene banks, or clone archives.…”
Section: Introductionmentioning
confidence: 99%